2014
DOI: 10.1177/0268355514552005
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study to optimise treatment of varicose veins with radiofrequency-induced thermo therapy

Abstract: Using low power (6 W) and a slow discontinuous pullback (6 s every 0.5 cm, in steps), we were able to achieve our target thermal ablation in the porcine liver model without carbonisation and high impedance cut outs. This suggests the currently recommended power levels could be reduced, reducing the need to remove the device to clean the electrodes during treatment while achieving target thermoablation of the treated tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 11 publications
0
45
0
Order By: Relevance
“…8 Numerous studies using radiofrequency ablation (RFA) were subsequently published. [9][10][11] Studies comparing endovenous laser ablation (EVLA) and RFA then began being published. These studies generally reported equal success between EVLA and RFA, albeit with fewer side-effects and greater patient satisfaction with RFA.…”
Section: Introductionmentioning
confidence: 99%
“…8 Numerous studies using radiofrequency ablation (RFA) were subsequently published. [9][10][11] Studies comparing endovenous laser ablation (EVLA) and RFA then began being published. These studies generally reported equal success between EVLA and RFA, albeit with fewer side-effects and greater patient satisfaction with RFA.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of three papers, we have shown that by modelling thermal spread from an endovenous thermal ablation device in porcine liver, 6 confirming the findings in an ex vivo vein can then lead to 100% ablation in the clinical setting at one year 7, 8…”
mentioning
confidence: 66%
“…In order to reduce the risks as far as possible, we consider that the RF-energised guidewire should be introduced into a venous rather than an arterial branch, as recently proposed for the ethanol injection [26]. The technical limitations could be related to the metallic guidewire sticking to the inner wall of the vessel, which has been observed in endovenous varicose vein RF-ablation [27]. Even though.…”
Section: Clinical Risks and Technical Limitationsmentioning
confidence: 99%